2012
DOI: 10.1007/s13758-012-0043-9
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Changes in Cell Morphology due to Cytoskeletal Rearrangements Measured in Real-Time by QCM-D

Abstract: The mechanical properties and responses of cells to external stimuli (including drugs) are closely connected to important phenomena such as cell spreading, motility, activity, and potentially even differentiation. Here, reversible changes in the viscoelastic properties of surface-attached fibroblasts were induced by the cytoskeleton-perturbing agent cytochalasin D, and studied in real-time by the quartz crystal microbalance with dissipation (QCM-D) technique. QCM-D is a surface sensitive technique that measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 52 publications
6
88
0
Order By: Relevance
“…Quartz crystal microbalance (QCM) transducers are widely used mass‐sensitive sensors in the field of biosensor design, where the acoustic wave platforms serve as sensitive elements during surface binding events . The QCM has been also successfully applied to study cell adhesion, the surface spreading of living cells, the interaction of antibody with growth factor receptors of cancer cells, and cell responses when exposed to nanoparticles and nanotubes . Tymchenko et al used the QCM with dissipation monitoring (QCM‐D) biosensor setup to study the biomechanical properties of stem cell CM clusters.…”
Section: Methods Results and Discussionmentioning
confidence: 99%
“…Quartz crystal microbalance (QCM) transducers are widely used mass‐sensitive sensors in the field of biosensor design, where the acoustic wave platforms serve as sensitive elements during surface binding events . The QCM has been also successfully applied to study cell adhesion, the surface spreading of living cells, the interaction of antibody with growth factor receptors of cancer cells, and cell responses when exposed to nanoparticles and nanotubes . Tymchenko et al used the QCM with dissipation monitoring (QCM‐D) biosensor setup to study the biomechanical properties of stem cell CM clusters.…”
Section: Methods Results and Discussionmentioning
confidence: 99%
“…17,18 As the decay length of the shear wave (about 250 nm for 5 MHz) is assumed to be less than the cell diameter (about 10 µm), this suggests that QCM-D probes the lower part of the cells close to the cell-substrate interface giving very high sensitivity to processes limited to the region where the actual adhesion occurs. 17 The penetration depth of the damped wave coupled to the resonator can be influenced by the viscosity, stiffness and shape of the attached cells, which in turn affects the QCM-D signals. Several groups demonstrated that the adhesion of cells onto the resonator surface induces a shift in frequency that scales linearly with the fraction of the surface covered with the cells.…”
Section: Monitoring Cell Adhesion By Qcm-dmentioning
confidence: 99%
“…This experimental approach offers several advantages compared to classical optical/confocal microscopy techniques that are limited by experimental errors due to sample‐light interactions or erroneous optical beam path inside the microscope and provide end‐point measurements, which result more time‐consuming and laborious for monitoring on‐going modifications . Although CytoD was widely used in the QCM study of various cells, Y27632 was studied for the first time by QCM‐D in this work.…”
Section: Introductionmentioning
confidence: 99%